PENDALAMAN DAN PENGEMBANGAN MATERI PAI BIDANG FIQIH DI MADRASAH TSANAWIYAH KELAS VII K13 - Zulaikah, Eni; Saifullah, Saifullah; Barni, Mahyuddin (CV. Lafadz Jaya, 2024)
This study aims to explore and develop Islamic Religious Education (PAI) materials in the field of fiqh taught in grade VII of Madrasah Tsanawiyah based on the 2013 Curriculum. Fiqh is one of the branches of science in Islam that studies the laws of Islamic law in depth. In the context of learning in Madrasah Tsanawiyah, fiqh material needs to be studied and developed to suit the times and the needs of students. This research uses a qualitative approach with the methods of literature study, observation of learning, and interviews with fiqh teachers and experts. Data were collected from relevant primary and secondary sources, such as fiqh books, PAI curriculum, and learning materials used in Madrasah Tsanawiyah. The results showed that the fiqh materials taught in the seventh grade of Madrasah Tsanawiyah are still general and less contextualized. Therefore, it is necessary to deepen and develop the material to make it more applicable and in accordance with the times, for example by adding examples of contemporary fiqh cases and linking them to the daily lives of students. This study provides recommendations on strategies for deepening and developing fiqh materials, as well as their implications for a more effective and meaningful PAI learning process for students.